Murine vs. Human Osteoblast Responses to Coagulation and Inflammatory Factors: Reconsidering the Use of Animal Models in Hemophilia a Research - Aline Bernar; Monika Bauer; Michael Schirmer; Werner Streif; Jennifer Gebetsberger (Biomedicines)
Background/Objectives: Hemophilia A is associated with frequent bleeding episodes, joint damage, and reduced bone mineral density (BMD). The role of coagulation factors and inflammatory cytokines on bone metabolism, particularly on osteoblast function, is of increasing interest. However, significant inter-species differences in bone remodeling raise concerns about the translatability of findings from murine models to human systems. This study aims to investigate the effects of human coagulation factors and cytokines on bone formation, focusing on inter-species differences in the cell viability and mineralization of murine and human osteoblasts. Methods: Murine MC3T3-E1 and human SaOs-2 osteoblasts were cultured in osteoblast differentiation medium supplemented with various coagulation factors (FVIII, vWF, vWF-FVIII, FIX, FX, thrombin, and FVIII-thrombin) or cytokines (IL-6, TNF-α). Cell viability was assessed at both two-week and three-week time points using the CCK-8 assay, and mineralization was evaluated via Alizarin red S staining. Results: Coagulation factors significantly enhanced cell viability in human osteoblasts but had no effects on the murine counterpart. FX inhibited mineralization in human cells, while murine cells showed no significant changes. TNF-α stimulated mineralization in murine osteoblasts but inhibited it in human cells, highlighting species-specific responses to inflammatory cytokines. Similar trends in response patterns were observed at two and three weeks, with greater consistency at the later time point. Conclusions: These findings reveal critical inter-species differences in osteoblast responses to coagulation factors and cytokines, raising questions about the validity of using murine models to study human bone metabolism. Future research must account for these differences to ensure that preclinical models accurately reflect human pathophysiology, particularly in the context of hemophilia A.